Halal Certification Guarantee for Food and Medicine Products (Human Rights Perspective) - Asmah Asmah; Ummu Salamah (International Journal of Halal System and Sustainability, 2021)
The Guarantee of Halal certificates for food and medicinal products is a must and an obligation. This aims to provide protection for consumers as well as a human right based on the belief in the religion and the rights that must be obtained as citizens. The method used in this paper is descriptive qualitative with a case approach and statutory regulations. The result of this study shows that halal certificates have a very important role not only for consumers but also for business actors. It becomes the part of the health rights for the citizens themselves and for their families as stated in the DUHAM.